THE INFLUENCE OF TBLT AND LEARNING MOTIVATION TOWARD WRITING ACHIEVEMENT TO THE ELEVENTH GRADE STUDENTS OF SMK N 3 PALEMBANG - Vivin Afini; Andika Andika; Arief Rahman Hakim (Esteem Journal of English Education Study Programme, 2021)
This research was conducted in experimental group with the total sample was 34 students of eleventh grade students of SMK N 3 Palembang in the second semester in the academic year 2016-2017 and it inquiry of the influence of TBLT and Learning Motivation toward Writing Achievements. The problem of this study is to find out the significance average score and motivation between TBLT and Conventional Technique. Due the interpretation of thisÂ  study, it found that: (1) there was a significant difference in writing achievement between the student who taught by using TBLT and those are taught using conventional technique (2) there was significant difference in writing achievement between the students who have high motivation by using task based language teaching and conventional technique (3) there was significant difference in writing achievement between the students who have low motivation by using task based language teaching and conventional technique 4) there was significant difference in writing achievement between the students who have low and high motivation by using task based language teaching and (5) there was an interaction effect of technique used and studentâ€™s motivation in improving writing achievement.